Knowledge, attitude and practices regarding legal and ethical standards in nursing practice among nurses at district hospitals in Namibia - Munenguni, Elise Taati (Stellenbosch : Stellenbosch University, 2024)
Thesis (MNur)--Stellenbosch University, 2024.